Rationale and design of the FreezeAF trial: a randomized controlled noninferiority trial comparing isolation of the pulmonary veins with the cryoballoon catheter versus open irrigated radiofrequency ablation in patients with paroxysmal atrial fibrillation - Luik, Armin; Merkel, Matthias; Hoeren, Danielle; Riexinger, Tobias; Kieser, Meinhard; Schmitt, Claus (American heart journal, 2010)
Atrial fibrillation is the most commonly encountered clinical arrhythmia, and there are an increasing number of patients with paroxysmal atrial fibrillation treated by catheter ablation. The criterion standard is the isolation of the pulmonary veins (PVs) using radiofrequency (RF) energy in combination with an open irrigated tip catheter. The procedure remains technically challenging with a significant number of complications. So far, no randomized comparisons between the outcome of cryoballoon versus RF ablation are available.